FinTech and financial stability: threat or opportunity? - Mohd Daud, Siti Nurazira; Ahmad, Abd Halim; Khalid, Airil; W. N., W. Azman Saini (Academic Press, 2022)
This paper investigates the relationship between FinTech countries’ financial stability in a panel of 63 countries from 2006 to 2017. We employed the dynamic panel of System Generalized Method of Moments (GMM) estimator that addresses possible endogeneity. The empirical results indicate that FinTech promotes financial stability through the channels of artificial intelligence, cloud technology, and data technology. Our findings also suggest that bank concentration complements the effect of FinTech on financial stability. In light of these findings, financial institutions should embrace FinTech and lead the way in evolving and creating an enabling FinTech ecosystem.